(untitled) (CIPEEX, 2025)
Childhood is a crucial phase for the formation of habits that last throughout life, especially regarding personal hygiene. Practical and habitual teaching of proper hand and body hygiene should be integrated into educational centers, particularly those serving the preschool age group, given the children’s ability to absorb what is taught at this stage. In this context, students from the Universidade Evangélica de Goiás developed a health education initiative at the Centro de Educação Infantil (CEI) in Anápolis, Goiás. Objective: To describe a public health project focused on deficiencies related to children’s hygiene, based on playful workshops focused on handwashing and bathing hygiene. Methodology: The criteria adopted followed the Maguerez Arc, which guided the stages of observing reality, identifying key points, theorizing, developing solution hypotheses, and applying them to reality. During the observation phase, the students identified that the lack of proper hand and body hygiene among children was a recurring problem. Based on the analysis of the collected information, it was concluded that there was a need for educational interventions that taught hygiene practices in a playful and interactive way. The theorization was based on studies that highlight the effectiveness of playful interventions in health education for children, considering factors such as target audience, applicability, and infrastructure. The activities conducted at the CEI involved dividing the students into two groups: one responsible for addressing hand hygiene and the other for bathing hygiene. The hand hygiene workshop included a relaxed chat, followed by a practical demonstration of proper washing using paint to illustrate the process, along with a song on the topic. The bathing hygiene workshop included a chat and used drawings of microorganisms pasted on one of the participants and later on the children so that they could simulate the act of "cleaning" with the help of a sponge, accompanied by children’s music and drawings. Results: The students were positively evaluated by both the university teaching staff and the CEI management team. Playful and dynamic activities, such as music, drawings, and simulations, facilitated learning and adherence to proper hygiene practices among children. The effectiveness of the "Criança Limpa, Criança Feliz" project highlighted the importance of integrating health education into school practices, especially from early childhood when habits are formed. Conclusion: The experience underscored the relevance of educational approaches tailored to the children’s audience and served as a practical example of the application of active methodologies, promoting well-being and possible disease prevention.